Flexure pitch bearing concept for individual pitch control of wind turbines. Issue 2 (16th November 2017) - Juettner, Michael; Hasse, Alexander; Tremmel, Stephan
Abstract: The excessive use of individual pitch control (IPC) for fatigue load reduction is accompanied by the uncertainty of potential bearing failures. This problem, which is due to the small swivel angles associated with IPC, arises because of the rolling and sliding contacts that occur with the rolling element bearings that are typically used. The use of a flexure bearing is proposed as a way of bypassing this issue. The flexure bearing enables a certain range of motion to be exclusively provided by elastic deformation. This article presents a novel bearing concept that is based on the hypothesis that such a flexure bearing can handle the unfavorable load conditions associated with IPC better than a rolling element bearing. Methods for the dimensioning of the aforementioned flexure bearing are therefore presented. The loads, particularly the required elastic rotation angle of the flexure bearing, are determined first. A promising design for the flexure bearing itself is then chosen and adapted to meet the specific requirements of IPC. These methods are applied to develop an initial conceptual design of the novel bearing unit for a 3‐bladed wind turbine of about 3.6 MW. The result demonstrates the feasibility of the concept, and a final discussion presents further opportunities of the design that will make this concept satisfy the special requirements of IPC.